Analysis of the Relationship between Work Motivation, Transformational Leadership, Organizational Culture, Job Satisfaction on Employee Performance in the Millennial Generation Workforce - Marvin Hendrily; Shandy Puspita (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to analyze the influence of work motivation, transformational leadership, organizational culture, and job satisfaction on employee performance among the millennial generation workforce. A quantitative descriptive-causal approach was employed, utilizing multiple regression analysis with the assistance of Statistical Package for the Social Sciences (SPSS). Data were collected through a Likert scale 1–5 questionnaire from 150 respondents for model testing and 305 respondents for instrument validity and reliability testing. The results indicate that work motivation has a significant and positive effect on employee performance. Transformational leadership does not have a significant direct effect on performance. Organizational culture has a significant but negative effect on performance. Job satisfaction is the most dominant variable, exerting a highly significant and positive influence on the performance of millennial generation employees. Simultaneously, all four variables significantly affect employee performance, with an Adjusted R Square value of 0.726, indicating that 72.6% of the variation in employee performance can be explained by the constructed model. These findings imply that organizations should prioritize strengthening job satisfaction and work motivation as primary strategies to sustainably enhance the performance of the millennial generation workforce.